2021
DOI: 10.3389/fimmu.2021.591706
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of LOC645166 in T Cells of Ankylosing Spondylitis Patients Promotes the NF-κB Signaling via Decreasingly Blocking Recruitment of the IKK Complex to K63-Linked Polyubiquitin Chains

Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory disease that mainly affects the spine. AS is highly associated with the expression of HLA-B27. Up to 95% AS patients are HLA-B27-positive. However, only 1%–2% of the HLA-B27-positive carriers suffer from AS, implying that other factors may also govern the development of AS. Long non-coding RNAs (lncRNAs) can regulate the immune response via their binding proteins. In the present study, we have identified that the levels of lncRNA, LOC645166, in T cells of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Yu et al demonstrated that LOC645166 was one of the most downregulated lncRNAs in T cells from AS patients as compared to those from healthy controls ( 68 ). Enforced expression of LOC645166 suppressed the expression of IL-23p19 (a subunit of IL-23) and inhibited JAK2/STAT3 signaling induced by phorbol 12-myristate 13-acetate or anti-CD28/CD3 antibodies in Jurkat cells (an immortalized line of human T lymphocytes).…”
Section: Lncrna Expression Profiling Studies In Asmentioning
confidence: 99%
“…Yu et al demonstrated that LOC645166 was one of the most downregulated lncRNAs in T cells from AS patients as compared to those from healthy controls ( 68 ). Enforced expression of LOC645166 suppressed the expression of IL-23p19 (a subunit of IL-23) and inhibited JAK2/STAT3 signaling induced by phorbol 12-myristate 13-acetate or anti-CD28/CD3 antibodies in Jurkat cells (an immortalized line of human T lymphocytes).…”
Section: Lncrna Expression Profiling Studies In Asmentioning
confidence: 99%
“…The total RNAs of NK-92MI cells were isolated by using the QIAamp RNA Blood Mini kit (QIAGEN, GmbH, Hilden, Germany). IFN-γ, TNF-α, or IL-6 mRNA amplified with real-time PCR using a One Step SYBR Ex Taq qRT-PCR kit (TaKaRa, Shiga, Japan) followed the methods [ 28 ]. Relative expression levels of mRNA were calculated with the following equation: (40−threshold cycle [Ct], adjusted by the expression of 18S rRNA).…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of miR-451 suppressed macrophage migration inhibitory factor (MIF) and levels of inflammatory cytokines (24). Yu et al (32) found that LOC645166 expression was downregulated in T cells from AS patients, which upregulated NF-kB activation by reducing the recruitment of polyubiquitin chains that block the IKK complex to K63 linkage, making AS patients more sensitive to stimulation by pro-inflammatory cytokines or TLR ligands. Li et al (33) showed that lncRNA maternally expressed gene 3 (MEG3) plays a partial anti-inflammatory role in AS by targeting miR-146a to regulate the expression of IL-1b, IL-6, and TNF-a.…”
Section: As Cell Inflammatory Responsesmentioning
confidence: 99%